Distal Transradial Access for Diagnostic Cerebral Angiography and Neurointervention: Systematic Review and Meta-analysis - Hoffman, H.; Jalal, M.S.; Masoud, H.E.; Pons, R.B.; Rodriguez Caamaño, I.; Khandelwal, P.; Prakash, T.; Gould, G.C. (American Journal of Neuroradiology, 2021)
BACKGROUND: Radial artery access for cerebral angiography is traditionally performed in the wrist. Distal transradial access in the anatomic snuffbox is an alternative with several advantages.PURPOSE: Our aim was to review the safety and efficacy of distal transradial access for diagnostic cerebral angiography and neurointerventions.DATA SOURCES: We performed a comprehensive search of the literature using PubMed, Scopus, and EMBASE.STUDY SELECTION: The study included all case series of at least 10 patients describing outcomes associated with distal transradial access for diagnostic cerebral angiography or a neurointervention.DATA ANALYSIS: Random-effects models were used to obtain pooled rates of procedural success and complications.DATA SYNTHESIS: A total of 7 studies comprising 348 (75.8%) diagnostic cerebral angiograms and 111 (24.2%) interventions met the inclusion criteria. The pooled success rate was 95% (95% CI, 91%–98%; I2 = 74.33). The pooled minor complication rate was 2% (95% CI, 1%–4%; I2 = 0. No major complications were reported. For diagnostic procedures, the combined mean fluoroscopy time was 13.53 [SD, 8.82] minutes and the mean contrast dose was 74.9 [SD, 35.6] mL.LIMITATIONS: A small number of studies met the inclusion criteria, all of them were retrospective, and none compared outcomes with proximal transradial or femoral access.CONCLUSIONS: Early experience with distal transradial access suggests that it is a safe and effective alternative to proximal radial and femoral access for performing diagnostic cerebral angiography and interventions. Additional studies are needed to establish its efficacy and compare it with other access sites.dTRAdistal transradial accessFTfluoroscopy timepTRAproximal transradial accessRAOradial artery occlusionTFAtransfemoral accessTRAtransradial accessUSultrasound